Resource Market Power and Levels of Knowledge in General Equilibrium - Waldemar Marz; Johannes Pfeiffer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2015)
We analyze monopoly power in a market for a complementary fossil resource like oil in a twocountry/two period model with international trade in general equilibrium. Focusing on thecomplex interplay of capital and resource market, we elaborate how these effects feed backinto the resource monopolist's extraction decision. His level of knowledge about the economicstructure thereby plays a key role. The accumulation of own capital assets over time, togetherwith a recognized influence of extraction on the interest rate, can lead the monopolist to accelerateor postpone extraction. Considering the interaction of resource market and globalcapital accumulation poses an incentive for the monopolist to accelerate extraction and toexploit the importers' increased resource addiction in the future. The conservationist bias ofresource market power can be increased, dampened or reversed through the general equilibriumeffects.
Keywords: D42; D58; D90; Q30; 330; Monopoly; fossil energy resources; Hotelling rule; general equilibrium; capital market; sovereign wealth